From national identity to state legitimacy: Mobilizing digitally networked publics in eastern Ukraine. (September 2020) - Boichak, Olga; Jackson, Sam
Social media enable broad and diverse publics to mobilize around a shared collective identity. In this article, the authors use social movement literature and studies of peace and conflict to foreground the role of platform-mediated communication in creating a national identity in a fragile state. We argue that, by affording activists with a possibility of public, yet anonymous interactions, social media may play a crucial role in conferring state legitimacy during a violent conflict. Investigating the case of Mariupol, Ukraine, where a small group of citizens employed social media to support and legitimize the Ukrainian state among the city population, the authors illuminate the use of new media affordances to construct a national identity among digitally networked publics, mobilizing support for a threatened state.